OP79 Medium term changes in household purchasing of soft drinks following the UK soft drinks industry levy by income and household composition: controlled interrupted time series analysis, March 2014 to November 2019. (26th August 2022) - Rogers, Nina; Pell, David; Cummins, Steven; Rutter, Harry; Sharp, Stephen; Smith, Richard; White, Martin; Adams, Jean
Abstract : Background: Consumption of sugar-sweetened beverages (SSBs) is associated with poor health outcomes and is more common in lower socio-economic groups and children. The UK soft drinks industry levy (SDIL, announced March 2016 and implemented April 2018) is associated with reductions in content of, and purchases of sugar from soft drinks 12 months post-implementation, but its longer term and distributional effects have not been reported. We examined changes in household purchasing of sugar in soft drinks overall and according to household income or presence of children in households, at 19 months post-implementation Methods: Take-home household purchases of soft drinks (levy eligible or not) across 295 weeks (March 2014-November 2019) were analysed using a commercial household purchasing panel (mean weekly number of households =21, 908). Interrupted time series (ITS) were used to estimate SDIL-related changes in purchased volume of, and sugar in, soft drinks, with toiletries as a control category. Counterfactual values were predicted based on pre-announcement trajectories. Differences between observed and counterfactual values were estimated by household income (<£20, 000, £20–50, 000 or >£50, 000) and presence of children (<16 years) in households (yes or no). Results: By November 2019, overall purchased sugar in soft drinks fell but volumes remained unchanged, compared to the counterfactual. In low-income households, weekly sugar purchased in soft drinks decreased by 14.0% (95%CI: 12.1, 15.9) compared to the counterfactual but increased by 3.4% (1.07, 5.75) in high income households. Among households with children, sugar purchased decreased by 13.7% (12.1, 15.3) compared to the counterfactual but increased in households without children by 5.0% (3.0, 7.0). Low-income households and those with children also reduced their weekly volume of soft drinks purchased by 5.7% (3.7, 7.7) and 8.5% (6.8, 10.2) respectively. There was no evidence of substitution to confectionary or alcohol in any groups. Discussion: In the second year, following implementation of the SDIL, there were sustained reductions in sugar from soft drink purchases. Effects were greatest in those with the highest pre-SDIL purchasing levels (low-income households and those with children), so the SDIL may contribute to reducing dietary inequalities. The trajectories of the counterfactuals used in the ITS were modelled and based on trends from March 2014 up until the SDIL announcement; however, we acknowledge they may not have continued to take the same course. Waste or the share of purchases among individuals within a household could not be recorded. Further studies using data on individual dietary intake would complement our findings.